2006
DOI: 10.1097/01.pas.0000213313.36306.85
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microsatellite Instability, CpG Island Methylation Phenotype, BRAF and KRAS Status in Serrated Polyps and Traditional Adenomas Indicates Separate Pathways to Distinct Colorectal Carcinoma End Points

Abstract: The aim of this study was to compare BRAF and KRAS, CpG island methylator phenotype (CIMP), and microsatellite instability (MSI) status in each of the histologic categories, including end-point carcinomas with residual adenoma, of the serrated polyp neoplasia pathway and the traditional (nonserrated) adenoma-carcinoma sequence. Deoxyribonucleic acid (DNA) was extracted from the selected samples and assayed for BRAF, KRAS2 codon12, 13, CIMP using markers hMLH1, MGMT, MINT1, MINT2, p16, and MSI using an assay fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
417
9
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 438 publications
(463 citation statements)
references
References 40 publications
29
417
9
8
Order By: Relevance
“…45,46 BRAF V600E mutations and CpG island methylation phenotype-positive status were more common in signet ring cell carcinoma and mucinous adenocarcinoma compared with conventional adenocarcinoma. Similar observations regarding BRAF V600E in signet ring cell carcinoma have been noted by Ogino et al 35 Expression of the gastric mucin MUC5AC, a typical feature of serrated polyps, is also more common in mucinous and signet ring cell carcinomas, but is relatively uncommon in conventional adenocarcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…45,46 BRAF V600E mutations and CpG island methylation phenotype-positive status were more common in signet ring cell carcinoma and mucinous adenocarcinoma compared with conventional adenocarcinoma. Similar observations regarding BRAF V600E in signet ring cell carcinoma have been noted by Ogino et al 35 Expression of the gastric mucin MUC5AC, a typical feature of serrated polyps, is also more common in mucinous and signet ring cell carcinomas, but is relatively uncommon in conventional adenocarcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, stepwise increment of AXIN2 methylation was identified from SSA/Ps (4%) through those with high-grade dysplasia (64%) to those with submucosal carcinoma (78%), indicating that AXIN2 methylation has an important role in the serrated neoplasia pathway as well as microsatellite instability associated colorectal carcinomas, some of which has been considered to be the end point of progression in the serrated pathway. [3][4][5] Loss of APC function by gene mutation or methylation is the reason for b-catenin translocation into the nucleus in the conventional adenomacarcinoma sequence. 18,25 The majority (60-91%) of conventional tubular adenomas or adenocarcinomas have APC mutations, 15,16 but to our knowledge no mutational study of APC has been conducted in SSA/Ps, although methylation of APC has been reported to be more frequent in tubular adenomas (56-65%) than SSA/Ps (22-25%).…”
Section: Modern Pathology (2015) 28 146-158mentioning
confidence: 99%
“…shown associations of SSA/P and those with dysplasia or carcinoma with methylation or loss of protein expression for DNA repair genes, ie, MLH1, 1,4,6-9 a CpG island methylator phenotype, 3,4,6,8 BRAF mutations, 3,4,[6][7][8][9][10][11][12][13][14] and a lack of genetic alterations in CTNNB1 (the gene coding for b-catenin protein). 14 This pathway is thought to be distinct from the conventional adenoma-carcinoma pathway, where adenomas progress to invasive colorectal carcinomas through the influence of a series of genetic alterations including adenomatous polyposis coli (APC) and KRAS mutations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF mutations were first assayed by allele-specific PCR (codon V600E) by previously described methods. [17][18][19] Two sets of allele-specific primers (forward and reverse gene coding strand) were designed to duplex with a single pair of GAPDH primers as DNA quality internal control to amplify the mutated allele. Following allele-specific PCR, direct DNA Sanger sequencing was used to confirm the mutation positive cases and a few allele-specific PCR failed cases (as indicated by negative GAPDH PCR).…”
Section: Dna Analysesmentioning
confidence: 99%